2018
DOI: 10.1007/978-981-10-1947-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Niche Strategies to Introduce Kite-Based Airborne Wind Energy

Abstract: Kite-based airborne wind energy systems are new high-tech systems that provide sustainable wind energy. Instead of using a wind turbine, these systems use a kite to generate energy. Commercializing such new high-tech systems is a risky strategy, the failure rate is high. This chapter identifies barriers that block large-scale diffusion of kite-based airborne wind energy systems and specific niche strategies to deal with these barriers. The results are based upon literature research and interviews with six acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Some authors already recognize that AWE could trigger opposition [101,102] and that understanding social acceptability issues is therefore key for developing and deploying the technology [57,[116][117][118][119]. It has even been suggested that the commercialization of AWE depends on creating a positive public vision of the technology [120]. More specifically, it was assumed that if the general public and key stakeholders perceive AWE negatively (e.g., have worries about lacking reliability and safety), it could reduce support for and investment in the technology and hinder its large-scale deployment.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors already recognize that AWE could trigger opposition [101,102] and that understanding social acceptability issues is therefore key for developing and deploying the technology [57,[116][117][118][119]. It has even been suggested that the commercialization of AWE depends on creating a positive public vision of the technology [120]. More specifically, it was assumed that if the general public and key stakeholders perceive AWE negatively (e.g., have worries about lacking reliability and safety), it could reduce support for and investment in the technology and hinder its large-scale deployment.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, some authors also recognize that AWE could trigger social resistance [82,83] and that understanding public responses is, therefore, key for the deployment of the technology [52,[91][92][93]. It has even been suggested that the commercialization of AWE depends on creating a positive public vision of the technology [94]. More specifically, if the public and key stakeholders negatively perceive AWE (e.g., due to worries about lacking reliability and safety), it could reduce support for and investment in the technology and hinder its large-scale deployment.…”
Section: Summary Of the Findings From The Literature Reviewmentioning
confidence: 99%
“…At the beginning of the 20th century, German engineer Aloys van Gries filed patents for the use of kites to use wind turbines at high altitudes. Around the 1970s, Hermann Oberth acted upon this idea as an alternative to fossil fuels and nuclear power when there was an energy crisis [2]. It took another 20 to 25 years for airborne wind energy systems (AWES) to acquire real interest because of growing awareness of global warming.…”
Section: Introductionmentioning
confidence: 99%